Bioeconomic impact of bull breeding soundness examination in cow-calf systems - Menegassi,Sílvio Renato Oliveira (2011)
It was evaluated the bioeconomic impact of the breeding soundness evaluation on beef cattle production in southern Brazil. Two similar production systems, with and without the use of breeding soundness evaluation, were compared during 4 years in the municipality of Júlio e Castilhos. The rate of unsound bulls in the first examination was 22.8%. By performing the examination, calf production increased by 31%, 13.8 calves/bull/year and 24 kg of calves/cow/year. The benefit/cost ratio on the investment with the breeding soundness evaluation was R$ 35.84. The breeding soundness evaluation improves bioeconomic aspects of beef cow-calf systems.